THE RELATIONSHIP BETWEEN GOOGLE SEARCH VOLUME AND FLOOD EVENTS IN INDONESIA: A GOOGLE TRENDS ANALYSIS - RESTI KINANTHI; Mochammad Iqbal (Program Studi Komunikasi dan Penyiaran Islam Fakultas Dakwah Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2023)
The increasing number of floods every year brings a wide impact; the average loss caused by floods every year reaches 4.64T (Rp). Information about floods is very important to improve the preparedness of people living in disaster-prone areas. If information can be provided when people have a high interest in learning, it can have a profound effect on increasing public knowledge. To carry out effective risk communication in flood disasters, knowledge about flood disaster patterns is needed, as well as knowledge about community behavior in seeking information. One of the people's behavior in searching for information can be seen from the Google Trends analysis. The purposes of this study are to analyse the relationship between public interest in finding information through google trends with the keyword